Handling Stunting in Indonesia: Challenges, Progress and Recommendations - Suparji; Wahito Nugroho, Heru Santoso; Surtinah, Nani (National Journal of Community Medicine, 2024)
Stunting is a nutritional problem that has an impact on children's growth and development. This article discusses the prevalence of stunting in Indonesia, the efforts made by the government, and Indonesia's position in dealing with the stunting problem. Data from various sources, including WHO and the Global Nutrition Report, is used to provide a comprehensive picture. In a global context, stunting affected approximately 144 million children under five years in 2019, with a higher prevalence in low- and middle-income countries . In Southeast Asia, Indonesia, the Philippines and Timor Leste have a high prevalence of stunting. Even though Indonesia has shown progress in reducing stunting rates, there are still challenges and targets that must be achieved. Indonesia's contribution to the global stunting problem, both in terms of causes and solutions. Efforts that have been made, such as improving nutrition for children and pregnant women, quality of health services, access to sanitation, and participation of all parties, are highlighted as important steps in dealing with stunting.